Quantitative Structure-Activity Relationship Studies for Potential Rho-Associated Protein Kinase Inhibitors - Giovanna Cardoso Gajo; Tamiris Maria de Assis; Letícia Cristina Assis; Teodorico Castro Ramalho; Elaine Fontes Ferreira da Cunha (Journal of Chemistry)
A series of pyridylthiazole derivatives developed by Lawrence et al. as Rho-associated protein kinase inhibitors were subjected to four-dimensional quantitative structure-activity relationship (4D-QSAR) analysis. The models were generated applying genetic algorithm (GA) optimization combined with partial least squares (PLS) regression. The best model presented validation values of r2=0.773, qCV2=0.672, rpred2=0.503, Δrm2=0.197, rm test2⁡⁡=0.520, rY-rand2=0.19, and Rp2=0.590. Furthermore, analyzing the descriptors it was possible to propose new compounds that predicted higher inhibitory concentration values than the most active compound of the series.